Correlations between some structural and functional brain parameters in subjects with high risk of schizophrenia - Lebedeva, I. S.; Tomyshev, A. S.; Akhadov, T. A.; Omeltchenko, M. A.; Semenova, N. A.; Mentschikov, P. E.; Bogdanova, E. D.; Kaleda, V. G. (Human physiology, 2017)
The study was aimed to the analysis of correlations between anatomic brain parameters and characteristics of neurophysiological and metabolic supportive mechanisms of cognitive functions in the patients with ultra-high risk of schizophrenia. The study comprised 30 young male patients and 30 age- and sexmatched mentally healthy subjects. We used the methods of diffusion-weighted tomography, single voxel proton MR spectroscopy, and oddball ERP recording. The statistically significant intergroup differences in the structural connectivity were confirmed in the anterior thalamic radiation of the left hemisphere. The diffusion abnormalities in this area were correlated with P 300 latencies and the level of γ-aminobutyric acid (GABA).